Linguistic diversity among Australian children in the first 5 years of life - Verdon, Sarah; McLeod, Sharynne; Winsler, Adam (My University, 2014)
Like many English-dominant nations, Australia has a rich history of cultural and linguistic diversity. This diversity is the result of a melting pot of languages including languages spoken by Australia's Indigenous people and languages added by European settlement and subsequent waves of migration from various parts of the world. Despite this rich history of linguistic diversity, little has been documented on the languages spoken by Australian children. The first three waves of data from 5107 children in the nationally representative Longitudinal Study of Australian Children were analyzed to consider language diversity among Australian children in the first 5 years of life. Data were collected from birth at 2-year intervals. At 0–1 year of age, 10.8% of children were reported to have a language other than English used as the main language in their home. When children were 2- to 3-years old, 16.7% were spoken to and/or used a language other than English, and 15.3% were spoken to and/or used a language other than English at 4–5 years of age. The most common languages spoken by Australian children when aged 4–5 years after English were Arabic, Italian, Greek, Spanish, and Vietnamese. Personal and environmental factors significantly associated with use of a language other than English at 4–5 years were parental use of a language other than English, and being a first- or second-generation migrant.
Speech, Language and Hearing
Keywords: Culture and language